New data for the 10 rare plant species of the Flora of the Republic of N Macedonia - Matevski, Vlado; Kostadinovski, Mitko; Ćušterevska, Renata; Matevska, Olivera; Cvetanoska, Sara; Cvetkoska, Cvetanka; Ivanova, Angela (Macedonian Journal of Ecology and Environment, 2023)
This article provides new data on the chorology of 10 taxa for the Flora of the Republic of North Macedonia - Ferulago macedonica (Štip - v. Testemelci; Demir Kapija - between v. Prždevo and Besvica), Ditrichia graveolens (Makedonski Brod - between v. Zdunje et v. Taževo; Valandovo-Sobri), Laphangium luteoalbum (Vinica - between v. Laki and v. Mitrašinci), Tolpis umbellata (Prilep - v. Krivogaštani; Demir Kapija), Dianthus ernesti-mayeri (Kratovo - v. Šlegovo, Zdravci Kamen), Euphorbia characias subsp. wulfenii (Ohrid - St. Jovan Kaneo; v. Konjsko; Prespa - Oteševo), Hypopitys monotropa (Pehčevo - Pehčevska River), Ranunculus lateriflorus (Kratovo - v. Stracin-Suvo Ezero; Sveti Nikole - v. Crnilište), Geum rivale (Osogovo - Sultan Tepe; Markova Stapka; Maleševski Pl. - Strednjačka Reka; Ajdučki Kladenec - Stredna; Nešova Koliba, Strednjacka Reka; Kadiica - Kopanata Voda; Plačkovica - Turtel; Kožuf: Adžibarica - Momina Čuka) and Potentilla supina L. (Kavadarci - v. Resava, Begnište - Begnište; Bitola - v. Lera; Struga - v. Kalište). They belong to 8 families of angiosperms (Angiospermae-Dicotyledonae). New localities for the mentioned taxa are listed expanding their range on the territory of the country.